A Mentored Critical Thinking and Writing Exercise in a Dental School Curriculum - Terry E. Hoover; Fred Fendler; Lucinda J. Lyon (Association of American Medical Colleges, 2012)
Abstract This resource is a mentored critical thinking and writing exercise for use in a dental school curriculum. It was created to help students learn to develop a problem statement, question, or hypothesis; perform an increasingly sophisticated search of peer-reviewed literature; read and critically assess information and evidence; formulate some conclusions about the information they discover; and write a short, original referenced paper of 1,500-2,500 words describing their findings. This resource is intended to extend over three academic quarters. The educational significance of this student exercise is the one-on-one faculty mentoring that is built into the assignment. Mentors model evidenced-based decision-making, such as the ability to search peer-reviewed literature, determine quality of evidence, and utilize this information in the decision-making process.